2021
DOI: 10.1016/s1470-2045(20)30591-x
|View full text |Cite
|
Sign up to set email alerts
|

Objective responses to first-line neoadjuvant carboplatin–paclitaxel regimens for ovarian, fallopian tube, or primary peritoneal carcinoma (ICON8): post-hoc exploratory analysis of a randomised, phase 3 trial

Abstract: Arm 2 (n=263) Arm 3 (n=259) Total (n=779) Age, years 65 (59-70) 62 (54-68) 64 (55-69) 64 (56-69) ECOG performance status 0 105 (41) 113 (43) 93 (36) 311 (40)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Conflicting outcomes were reported about the predictive value of the radiological response regarding the probability of complete IDS, or patient prognosis [46,47]. A recent analysis of the ICON-8 phase III trial dataset on 1566 patients confirmed that the radiological response assessed with the Response Evaluation Criteria in Solid Tumors (RECIST) was not an appropriate parameter to assess the efficacy of the neoadjuvant chemotherapy and predict the benefit from IDS [48].…”
Section: Indicators Of Tumor Primary Chemosensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting outcomes were reported about the predictive value of the radiological response regarding the probability of complete IDS, or patient prognosis [46,47]. A recent analysis of the ICON-8 phase III trial dataset on 1566 patients confirmed that the radiological response assessed with the Response Evaluation Criteria in Solid Tumors (RECIST) was not an appropriate parameter to assess the efficacy of the neoadjuvant chemotherapy and predict the benefit from IDS [48].…”
Section: Indicators Of Tumor Primary Chemosensitivitymentioning
confidence: 99%
“…The Gynecologic Cancer Intergroup (GCIG) defined the CA-125 response as a 50% reduction in CA-125 levels maintained for at least 28 days, in patients treated for recurrent diseases [49,50]. Different studies, including a recent analysis of the ICON-8 phase III trial dataset showed that this criterion was inadequate for assessing the efficacy of the neoadjuvant chemotherapy and predicting the benefit from IDS [48,51,52].…”
Section: Indicators Of Tumor Primary Chemosensitivitymentioning
confidence: 99%
“…More recently, Morgan et al reported the lack of accuracy of the GCIG criterion to identify the patients who were likely to benefit from interval debulking surgery (IDS) after neoadjuvant chemotherapy for EOC in the first-line setting of the phase III ICON-8 trial [ 14 , 20 ]. For example, a complete cytoreduction was achieved in 30 of 101 women (30%) without a GCIG CA-125 response and in 290 of 576 women (50%) who experienced a GCIG CA-125 response.…”
Section: Limitations Of the Gcig Ca-125 Response Definitionmentioning
confidence: 99%
“…The Gynecologic Cancer InterGroup (GCIG) defined the CA-125 response as a 50% reduction in CA-125 levels maintained for at least 28 days, in patients treated for recurrent disease [ 13 ]. However, the relevance of the GCIC criteria was recently questioned in the analyses of the CALYPSO trial in the recurrent setting and of ICON-8 trial in a first-line setting [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is a standard first‐line therapy for various types of cancer 1–3 . However, chemotherapeutic agents, such as oxaliplatin, paclitaxel and vincristine, are neurotoxic 4–6 .…”
Section: Introductionmentioning
confidence: 99%